The inner conflicts in The Scarlet Letter by Nathaniel Hawthorne - Ali Baram Mohammed; Salam Hussein Yahya (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The objective of this study is to explore the emotional reactions and internal conflicts of the main characters brought about by external events in “The Scarlet Letter” by Nathaniel Hawthorne. Further, the present study depicts all the mental agonies and inner struggles that the characters go through. The study also attempts to step inside the characters’ psyche to decipher the real motives behind the characters’ actions or, sometimes, the motives behind their reactions. To what extend does the public humiliation incline the characters to reveal or conceal their true feelings and real identities? Furthermore, it delves deeply into the complex mentalities of the four main characters: Hester Prynne, Arthur Dimmesdale, Roger Chillingworth and Little Pearl. The study, nonetheless, concentrates upon the idea that a single sin can condemn the past and determine the future of the characters. Hester Prynne, in the Puritan society, commits the act of adultery with her unknown partner-in-sin and her husband Chillingworth promises to seek revenge upon her secret lover. Further, the themes of isolation and alienation, which are an inevitable result from the act of adultery and deep internal feelings of guilt, will be explicated in this paper.